A longitudinal study of C1q and anti-C1q autoantibodies in homologous and heterologous pregnancies for predicting pre-eclampsia - Agostinis, Chiara; Zito, Gabriella; Toffoli, Miriam; Peterlunger, Isabel; Simoni, Livia; Balduit, Andrea; Curtolo, Erica; Mangogna, Alessandro; Belmonte, Beatrice; Vacca, Davide; Romano, Federico; Stampalija, Tamara; et al. (Frontiers in Immunology, 2022)
C1q, the recognition molecule of the classical pathway of the complement system, plays a central role in pregnancy. Lack of C1q is characterized by poor trophoblast invasion and pregnancy failure. C1q can be the target of an antibody response: anti‐C1q autoantibodies (anti-C1q) are present in several infectious and autoimmune diseases. The presence of these autoantibodies has been detected also in 2-8% of the general population. Recent evidence indicates that women who undergo assisted reproductive technology (ART) have an increased risk of developing pre-eclampsia (PE), particularly oocyte donation (OD) pregnancies. The aim of this study was to characterize the levels of C1q and anti-C1q in PE gestations, in healthy spontaneous, homologous and heterologous ART pregnancies. Serum of the following four groups of women, who were followed throughout two or three trimesters, were collected: PE, patients diagnosed with PE; OD, oocyte donation recipients; HOM, homologous ART women; Sp, spontaneous physiological pregnancy. Our results indicate that PE patients have lower levels of anti-C1q. In ART pregnant women, the trend of C1q and anti-C1q levels were similar to PE patients, even though these women did not develop PE-like symptoms during pregnancy. This finding suggests an immunological dysfunction at the foetal-maternal interface in ART pregnancies, a hypothesis confirmed by the observation of C1q deposition in placentae derived from OD, comparable to PE. Since significantly lower levels of anti-C1q were detected in PE compared to healthy control sera, we hypothesize the possible binding on placental syncytiotrophoblast microvesicles (STBM), which are increased in the circulation of PE mothers. Furthermore, the characterization of the binding-epitope of anti-C1q revealed that “physiological” autoantibodies were mainly directed against C1q globular domain. We concluded that anti-C1q could have a physiological role in pregnancy: during the healthy spontaneous pregnancy the raised levels of these autoantibodies can be important for the clearance of STBM. In PE and in pathological pregnancies (but also in OD pregnancies), the increase in syncytiotrophoblast apoptosis and consequent increase of the circulating STMB levels lead to a consumption of C1q and anti-C1q.